Cipp Evaluation Of Project Based Learning Cooking Class Program In Vocational Culinary Education For Early Childhood Learning - Erinna Ayu Prasysta; Laili Hidayati (Universitas Negeri Padang, 2026)
This study aims to evaluate the implementation of the Project Based Learning (PjBL) Cooking Class program of the Culinary Department of SMK Negeri 2 Malang at ABA 25 Kindergarten, Malang City using the CIPP (Context, Input, Process, Product) evaluation model. The study used a qualitative evaluative approach involving 12 informants consisting of supervising teachers, grade X students of the Culinary Department, the kindergarten principal, kindergarten teachers, and kindergarten students. Data collection techniques were carried out through in-depth interviews, participatory observation, documentation, and triangulation of sources, techniques, and time. Data were analyzed using the interactive model of Miles and Huberman through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the program contextually has high relevance to the vocational education curriculum and the learning needs of early childhood. In the input aspect, program planning has been running well although there are still limitations in facilities and infrastructure for implementing activities. In the process aspect, program implementation is effective with the active involvement of students in project-based learning. In the product aspect, the program has a positive impact on improving technical skills, communication, creativity, cooperation, and students' self-confidence. The study concluded that the PjBL Cooking Class program is effective as a project-based vocational learning model, but still requires strengthening of practical facilities, improving students' problem-solving skills, and a more structured program monitoring system.